Using Arima Models To Forecast A Wheat Production In Syria (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The aim of this study was to apply Box- Jenkins methodology represented by ARIMA models, to forecast a production of wheat in Syria, and to know if this model is effective in forecasting.The main results were: -The time series for the production of wheat in Syria for the period 1990 - 2016 is unstable, and then stabilized after making the second differences.- ARIMA (1,2,0) model, which is the suitable model to forecast a production of wheat, and it is effective model.- Forecasting the production of wheat in Syria for next third years.